Psychological Responses and Coping Mechanisms of Gay Men in Adapting HIV/AIDS: A Qualitative Study - Silalahi, Malianti; Fitriani, Nurlaila (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: This study explores the psychological responses and coping mechanisms employed by gay men in adapting to HIV/AIDS. Methods: This research is qualitative research with descriptive methods. The sample was taken using a purposive sampling technique with inclusion criteria, namely: gays who were declared positive for HIV/AIDS as proven by a doctor's statement stating that they were positive for COVID-19, were undergoing medical treatment both inpatient and outpatient, had experience interacting with nurses when undergoing treatment. This study involved four key informants to recruit potential participants who meet the inclusion criteria. Data analysis involved thematic analysis. Results: 14 participants were included. Four themes emerged: (1) anxiety and stress arising from interpersonal conflicts post-diagnosis, (2) diverse stages of the grieving process, (3) feelings of helplessness confronting the reality of HIV/AIDS, and (4) utilization of problem-solving coping mechanisms as a means of acceptance. Conclusion: The study emphasizes the importance of empowering gay men with HIV/AIDS by facilitating access to healthcare and social support. Empowerment enhances their ability to leverage internal resources to manage the disease, ultimately aiding them in leading more fulfilling lives.